Juridical Review of Registered Trademarks on Trademark Disputes Similarities in Principal (Decision Number: 83/Pdt.Sus-HKI/MEREK 2023/PN Niaga Jkt.Pst) - Handayani, Roslina; Gayatri, Almirah Syifa; Pakpahan, Marlina Elisabeth (Dinasti Research, 2025)
A trademark is something attached to a product is noticed also respected by the state through guaranteed ownership rights, so not just anyone can obtain intellectual property rights. If someone wants to be legally recognized as a brand owner, then they are obliged to register their trademark. The protection of such trademarks indicates the state is obliged to enforce trademark laws. There is legal protection for trademark owners to provide exclusive rights for brand owners (exclusive rights) so other business actors cannot use the same trademark as they own. The problems discussed in this study are about How to Regulate Trademark Registration As per Law No. 20 of 2016 concerning Trademarks also Geographical Indications, How to Legal Protection for Registered Trademarks Have Similarities in Essence, also How to Consider the Judge in Decision Number: 83/Pdt.Sus- HKI/MEREK 2023/PN Niaga Jkt.Pst. This studyuses normative studymethods. The data used are secondary data obtained through literature studies, laws also regulations, legal journals, also lecture materials related to this research.